Surface stability and morphological transformations of CsPbI3 - Laranjeira, José A.S. [UNESP]; Azevedo, Sérgio A.; Fabris, Guilherme S.L.; Sambrano, Julio R. [UNESP]; Ferrer, Mateus M. (Elsevier, 2024)
Metal-halide perovskites, particularly inorganic cesium-lead halide perovskites, have emerged as exceptional candidates for several technological applications in the 21st century, such as photovoltaic devices, optoelectronic and photocatalysis. This study systematically investigates the CsPbI3 surfaces through density functional theory (DFT) simulations and morphological analyses. The (0 0 1), (1 1 0), and (1 1 1) surfaces were investigated in terms of their possible terminations (here named α, β, γ, δ and ε), where the relations between their outermost coordination polyhedra, bond lengths, charge distribution, electronic and morphological properties were revealed. The results demonstrate that the (0 0 1) and (1 1 0) surfaces stand out as the most stables, with Esurf001-α=Esurf110-γ=0.08J/m2. Concerning the electronic properties, it is observed that the (1 1 0) and (1 1 1) present α terminations with acceptor states, while the β with donor states, making it possible to tune the system semiconducting behavior (n or p-type) via surface termination control. The Wulff construction was employed to show that (0 0 1), (1 1 0) and (1 1 1) surface stabilizations can produce cubic, dodecahedral and octahedral nanocrystal morphologies, respectively. By probing the depths of CsPbI3 surfaces, this research advances new concepts about the design and functionalization of perovskite halide, offering a crucial direction for experimental synthesis strategies.
Keywords: CsPbI3; DFT; Halide; Nanoparticle; Perovskite; Surface; Wulff